Design of a Dual-Band Shared-Aperture Array Antenna Composed of Array Elements With High Electromagnetic Transparency - Jiyoung Park; Doyoung Jang; Hosung Choo; Sungsik Wang (IEEE Access, 2024)
In this paper, we propose a dual-band shared-aperture antenna composed of array elements with high electromagnetic (EM) transparency. To increase EM transparency, the antenna consists of an optimized substrate with low effective permittivity by combining thin dielectric sheets and air-gap layers. To further improve the EM transparency, thin dual-loop radiators with optimized widths and lengths are adopted for the S-band element, and an E-shaped patch antenna is employed for an X-band element. This configuration minimize the pattern distortion in the X-band elements while enhancing antenna bandwidths. In addition, a calibration layer comprising four monopole probes and microstrip transmission lines is included for monitoring the phase and amplitude errors of each element. To verify the feasibility, the proposed antenna is fabricated to measure antenna characteristics, such as reflection coefficients, beam steering performance, and mutual coupling in a full anechoic chamber. The fractional bandwidths of the antenna in the S- and X-bands are 16.4% and 26.8%, respectively. The array gains at the bore-sight are 16.0 dBi in the S-band and 24.0 dBi in the X-band.